Fundamentals of Entrepreneurship ENT300 : Merzazusa Car Rental / Muhammad Zaki Pauz... [et al.] - Pauzi, Muhammad Zaki; Esa, Emmanuel Sumok; Amat@Sabi, Mohd. Marzuki; Siros, Muhammad Ameer Idzat (2015)
The Merzazusa car rental management team will be leads by General Manager who is responsible on preparing the business plan for the business agreed upon that to be opened, leading the other assisting management, organizing the task to be given to the assisting management, and controlling the task run by the assisting management. The marketing manager, on the other hand, will the one with the biggest responsibility on preparing the business marketing plan which includes the marketing process on identifying the target market, determining the market size, identifying the market competitors, determining the market share, developing sales forecast and finally marketing strategies. The operating manager will be the one who controlling and monitoring the business operating hour as well as noting the equipment and facilities that will be required in the Merzazusa car rental. Administration Manager is the one who is responsible for the office administration that involve the work of recruiting workers and office admin which will be establish soon. Last but not least, the finance Manager will be the most important person in our management as he is the person that will be managing the finance of Merzazusa car rental company from the budget he will distributed and final financial statement made that will be the peak point of the success or not of the business. This Merzazusa will give us chance to gain profit. It is normal at the early stage of business our company do not gain profit. The reason why our business should be go on because we have a strategic place which near with education place. Instead that our target are students. We believe that our business can be develops.